Sport Entrepreneurship Developing and Sustaining an Entrepreneurial Sports Culture - Ratten, Vanessa (Management for Professionals,, 2018)
This book introduces the structure, economic arguments, and business strategies for entrepreneurship in sport. Here, the entrepreneurial process is usually initiated by organizations, people or governments who are embedded in both economic and social contexts. The development of technologies that have enhanced the diffusion of information and the creation of new international markets has impacted sports entrepreneurship activities. The goal of this book is to introduce readers to emerging issues in sport entrepreneurship and management. The book focuses on the role of entrepreneurship in the sports context by examining how to leverage the opportunities that arise from networks and optimize resources by identifying where they can most effectively be put to use. As a unique discipline, sport entrepreneurship helps to identify the conditions under which and the processes in which upcoming business ventures need to be pursued. The book will be useful for sports organizations, athletes and government organizations promoting the use of entrepreneurship to generate competitive advantages on the global marketplace.